Dopaminergic System Alteration in Anxiety and Compulsive Disorders: A Systematic Review of Neuroimaging Studies - Dong, Mei-Xue; Chen, Guang-Hui; Hu, Ling (Frontiers in Neuroscience, 2020)
Objective Dopaminergic system is involved in many psychiatric disorders as GABAergic, serotonergic and glutamatergic system. A systematic review and meta-analysis was performed to elucidate the alteration of dopaminergic system in anxiety and compulsive disorders. Methods The databases of Pubmed, Embase, and ScienceDirect were searched and articles reporting the involvement of dopaminergic system in patients with anxiety disorder and obsessive compulsive disorder (OCD) were recognized. The key research data were extracted from the included articles and standardized mean differences were calculated using meta-analyses if there were more than 2 studies with obtainable data. Sensitivity analyses were further performed to detect the stability of results, and the qualities of all included studies were assessed using Newcastle Ottawa scale. Results Finally, we identified 8 and 11 studies associated with anxiety disorder and OCD for further analysis, separately. Most consistently, striatal dopamine D2 receptor (D2R) of OCD patient had decreased while no significant correlation can be found between striatal D2R and disease severity. Striatal dopamine transporter (DAT) had not significantly altered in both anxiety disorder and OCD patient. The heterogeneity values from meta-analyses were extremely high while those results remained stable after sensitivity analyses. Inconsistent data were found in striatal D2R of patients with anxiety disorder. Limited data had suggested that dopamine synthesis increased in most regions of cerebral cortex and cerebellum in OCD patients. Conclusions The most convincing finding is that D2 receptor has decreased in patient with obsessive compulsive disorder. Dopamine transporter may have no relationships with anxiety and compulsive disorder.